Fate of fertilizer N applied to maize intercropped with forage grass and recovery of residual N by soybean in a double cropping system - Gazola, Bruno [UNESP]; Mariano, Eduardo [UNESP]; Andrade, Maria G. O. [UNESP]; Costa, Vladimir E. [UNESP]; Rosolem, Ciro A. [UNESP] (Springer Nature, 2024)
Background and aims: Understanding the fate of nitrogen (N) in maize (Zea mays L.) intercropped with tropical grass is essential to develop sustainable fertilization recommendations and mitigate greenhouse gas emissions. To test the hypothesis that intercropping forage grass with maize improves yield and fertilizer N recovery in the system, this study evaluated the recovery of N applied to maize intercropped with forage grass grown as a double crop after soybean [Glycine max (L.) Merrill]. Methods: A two–year field experiment was conducted. In each season maize was intercropped with either Guinea grass (Megathyrsus maximus; syn. Panicum maximum) or ruzigrass (Urochloa ruziziensis; syn. Brachiaria ruziziensis) in southeastern Brazil in the presence or absence of N fertilization, followed by a soybean crop. 15N–enriched ammonium sulfate was used to trace the fate of the applied N. Results: Total recovery of fertilizer N by maize differed with season (≈ 35 and 22%) and was greater in the grain than vegetative fractions. Uptake of fertilizer N by intercropped forage grass was less than maize but substantial (≈ 11–18%) After maize harvest more than 60% of the N applied remained in the system, partly in forage grass and maize residues but mostly in soil. Up to 12% of the N applied was recovered by soybean grown in succession. Conclusion: The introduction of either Guinea grass or ruzigrass intercropped with maize can decrease N losses from fertilizer and increase recovery by soybean grown after maize, particularly when maize yield and N uptake are low.
Keywords: 15N; Forage grasses; Integrated cropping system; Nitrogen use efficiency